Antibiotic resistance: calling time on the 'silent pandemic'. Issue 2 (18th March 2022) - Mendelson, Marc; Sharland, Michael; Mpundu, Mirfin
Abstract: It is time to stop referring to the antibiotic resistance pandemic as 'silent'. Continuing to use such a term denies the reality that antibiotic-resistant bacterial infections, driven by misuse and abuse of antibiotics by humans against microbial ecosystems that we should be living in symbiosis with, is wrong. Both our terminology and who the real 'enemy' is in relation to antibiotic resistance demands serious reconsideration.